RANCANG BANGUN SISTEM INFORMASI PENJUALAN DAN LAYANAN JASA VARIASI DENGAN MENGGUNAKAN METODE EXTREME PROGRAMMING PADA LOTUS VARIASI - Naomi; Sudirman; Afifah (STMIK KHARISMA Makassar, 2018)
This study aims to design a system that can help the Lotus Variasi in handling the management of sales and service variations of the car using the method of Extreme Programming. To obtain data and information that support the implementation of this research, conducted observations and interviews. Information System implemented using Visual Basic 6.0 and Microsoft Access as data processing, then tested using black box testing method. With the new system is expected Lotus Variasi owners can run the sales process and service variation services.